Optimal Management For Waters For The Production Of Electrical Energy - Bensalem, A.; Oudai, A.; El-maouhab, A.; Bouhentala, A. (University of Eloued جامعة الوادي, 2010)
The hydropower management along a short-term planning horizon is a determinist problem, which consists in determining the amount of water to be discharged from each reservoir of the system over the defined planning horizon so that to meet the hourly load demand assigned previously. The prime objective here is to perform the operating policy with the lowest use of water; which is achieved by avoiding spilling and by maximizing the hydroelectric generation, besides satisfying all operating constraints. The maximization of electrical power production is achieved by maximizing the heads. Consequently, this allows maximizing the reservoirs content. To solve to the deterministic hydropower management problem, we use the discrete maximum principle. While solving the equations relating to the discrete maximum principle, we use the gradient method. However, to treat equality constraints we use Lagrange’s multiplier method. To treat the inequalities constraints we use the augmented Lagrangian method. The developed algorithm gives a satisfactory solution for the problem and turns out to be very efficient.
Articale in Journal of fundamental and Applied Sciences Vol. 02 N. 01
Keywords: Hydropower management, Optimal short-term scheduling, Potential energy, Planning horizon, Discrete maximum principle, Augmented Lagrangian method.